Monitoring for Photovoltaic in Outer Island - W Sunanda, E A Pratama, H Subastiyan, Y Tiandho, D Novitasari (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
Photovoltaic is a renewable energy source that can optimally be used on outer islands and areas that are difficult to reach by the main electrical system network. With good solar energy intensity on a daily, it adds to the advantages of using photovoltaics. In this regard, it is necessary to make a prototype for monitoring the photovoltaic output parameters to measure photovoltaic performance. The parameters that will be monitored on 50 Wp photovoltaic used in this research are voltage using a voltage sensor, current using an ACS712 sensor, and the real power generated. The monitoring results are stored in a database and monitored in realtime based on the website's setting. So that this prototype can be used in several outer islands in Bangka Belitung, which is geographically an archipelago